COMPARISON OF SITA STANDARD 24-2 WITH SITA FASTER 24-2C PROGRAM ON HUMPHREY FIELD ANALYZER IN ASSESSING VISUAL FIELD DEFECTS OF GLAUCOMA PATIENTS - Rianti, Nuzul; Satari, Karmelita; Prahasta, Andika; Rifada, R. Maula; Umbara, Sonie (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction: Periodical perimetry examination to detect and determine the rate of glaucoma progression continues to be a challenging task, because it depends on many factors. Besides, there is now a paradigm shift which central visual field defects occur earlier. SITA Standard (SS) 24-2 is the clinical standard for glaucoma examination, but there were studies reporting on the prevalence of central visual field defects not detected. SITA Faster (SFR) 24-2C was developed to address current shortcomings, but the performance has yet to be formally and independently assessed. Objective: To compare the global indices (Mean Deviation, Pattern Standard Deviation, Visual Field Index) and test duration between SS 24-2 and SFR 24-2C program. Methods: This is an analytical observational study with a cross-sectional design. Subjects aged >18 years who diagnosed with glaucoma and whose visual fields unaffected by other condition besides glaucoma were included. All subjects underwent testing of both programs. Results: This study was conducted in 94 eyes of 66 patients. Comparison of global indices and test duration between the two programs was carried out by the Wilcoxon test. The mean results of MD and PSD global indices were not significantly different, however there was a difference in the mean VFI of 1.5% between the two programs. The test duration of SFR 24-2C was 55.03% faster. Conclusion: There was no significant difference in the MD and PSD global indices, but there was a significant difference in the VFI, as well as the test duration between the two programs.